Draft Annual Plan 2011-2012 West Bengal - Planning Commission (Planning Commission, 2011)
Programme of the Agriculture Department 2011-12 is the closing year of XIth five year plan period. The target set at the onset of this plan period to take the growth of Agriculture beyond 4%. Due to natural calamities like devastating AIL A and coming of monsoon in latter part of the Kharif season normal production of foodgrains crops of the state has been hampered almost every year. The SDP at constant 1999-00 prices of the agricultural sector in the State had a dip in 2008-09. It had experienced a fall by 1.90% during 2008-09 (Economic Review 2009-10). But in the year 2009-10 inspite of natural calamities like AILA the production and productivity of wheat, pulses and oilseeds and potato have been increased resulting a positive gain in NSDP. During the year 2010-11 the monsoon is being delayed like previous years.
Development and Planning Department Government of West Bengal